Local bumble bee decline linked to recovery of honey bees, drought effects on floral resources. (19th August 2016) - Thomson, Diane M.
Abstract: Time series of abundances are critical for understanding how abiotic factors and species interactions affect population dynamics, but are rarely linked with experiments and also scarce for bee pollinators. This gap is important given concerns about declines in some bee species. I monitored honey bee ( Apis mellifera ) and bumble bee ( Bombus spp.) foragers in coastal California from 1999, when feral A. mellifera populations were low due to Varroa destructor, until 2014. Apis mellifera increased substantially, except between 2006 and 2011, coinciding with declines in managed populations. Increases in A. mellifera strongly correlated with declines in Bombus and reduced diet overlap between them, suggesting resource competition consistent with past experimental results. Lower Bombus numbers also correlated with diminished floral resources. Declines in floral abundances were associated with drought and reduced spring rainfall. These results illustrate how competition with an introduced species may interact with climate to drive local decline of native pollinators.